A Live-Attenuated Equine Influenza Vaccine Stimulates Innate Immunity in Equine Respiratory Epithelial Cell Cultures That Could Provide Protection From Equine Herpesvirus 1 - Zarski, Lila M.; Vaala, Wendy E.; Barnett, D. Craig; Bain, Fairfield T.; Soboll Hussey, Gisela (Frontiers in Veterinary Science, 2021)
Equine herpesvirus 1 (EHV-1) ubiquitously infects horses worldwide and causes respiratory disease, abortion, and equine herpesvirus myeloencephalopathy. Protection against EHV-1 disease is elusive due to establishment of latency and immune modulatory features of the virus. These include modulation of interferons, cytokines, chemokines, antigen presentation, and cellular immunity. Because modulation of immunity likely occurs at the site of first infection – the respiratory epithelium, we hypothesized that the mucosal influenza vaccine Flu Avert® I.N. (Flu Avert), which is known to stimulate strong antiviral responses, will enhance antiviral innate immunity and that these responses would also provide protection from EHV-1 infection. To test our hypothesis primary equine respiratory epithelial cells (ERECs) were treated with Flu Avert and innate immunity was evaluated for 10 days following treatment. The timing of Flu Avert treatment was also evaluated for optimal effectiveness to reduce EHV-1 replication by modulating early immune responses to EHV-1. Induction of interferons, cytokine and chemokine mRNA expression, and protein secretion was evaluated by high throughput qPCR and multiplex protein analysis. Intracellular and extracellular EHV-1 titers were determined by qPCR. Flu Avert treatment resulted in modulation of IL-8, CCL2 and CXCL9 starting on days 5 and 6 post treatment. Coinciding with the timing of optimal chemokine induction our data also suggested this timing for reduction of EHV-1 replication. In combination, our results suggest that Flu Avert may be effective at counteracting some of the immune-modulatory properties of EHV-1 at the airway epithelium, and the peak for this response occurs 5-8 days post Flu Avert treatment. Future in vivo studies are needed to investigate Flu Avert as a prophylactic in situations where EHV-1 exposure may occur.